2013
DOI: 10.1016/j.immuni.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The CD27 and CD70 Costimulatory Pathway Inhibits Effector Function of T Helper 17 Cells and Attenuates Associated Autoimmunity

Abstract: T helper 17 (Th17) cells protect against infection but also promote inflammation and autoimmunity. Therefore, the factors that govern Th17 cell differentiation are of special interest. The CD27 and CD70 costimulatory pathway impeded Th17 effector cell differentiation and associated autoimmunity in a mouse model of multiple sclerosis. CD27 or CD70 deficiency exacerbated disease, whereas constitutive CD27 signaling strongly reduced disease incidence and severity. CD27 signaling did not impact master regulators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
107
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 50 publications
15
107
3
Order By: Relevance
“…This finding is consistent with a recent report that CD27 signaling reduced the incidence and severity of disease in an EAE model. 188 Therefore, we hypothesized that despite certain phenotypic features of advanced maturation, considerable multipotency and plasticity demonstrated by Th17 cells indicated that these cells are not terminally differentiated, at least when induced in vitro. Despite their phenotype, Th1 cells might represent a more differentiated subset with less capacity to expand, persist, and eliminate tumors in vivo (Figure 3).…”
Section: 185mentioning
confidence: 99%
“…This finding is consistent with a recent report that CD27 signaling reduced the incidence and severity of disease in an EAE model. 188 Therefore, we hypothesized that despite certain phenotypic features of advanced maturation, considerable multipotency and plasticity demonstrated by Th17 cells indicated that these cells are not terminally differentiated, at least when induced in vitro. Despite their phenotype, Th1 cells might represent a more differentiated subset with less capacity to expand, persist, and eliminate tumors in vivo (Figure 3).…”
Section: 185mentioning
confidence: 99%
“…−/− and CD70 −/− , and reduced Th17 in CD70-Tg mice (124). They concluded that this increased Th17 differentiation in CD27…”
Section: Cd70-cd27mentioning
confidence: 95%
“…−/− and CD70 −/− animals were due to increased phosphorylation of the JNK and epigenetic modification at IL-17 locus, suggesting that CD70-CD27 signaling directly controls the Th17 response in CD4 + T cells (124). Interestingly, anti-CD70 antibody-mediated blocking of CD70 prevented EAE in SJL/J mice (121), and over-expression of CD70 on the B cells enhanced EAE (126).…”
Section: Cd70-cd27mentioning
confidence: 97%
See 2 more Smart Citations